2023
DOI: 10.5194/os-19-453-2023
|View full text |Cite
|
Sign up to set email alerts
|

Intraseasonal variability of the South Vietnam upwelling, South China Sea: influence of atmospheric forcing and ocean intrinsic variability

Abstract: Abstract. The South Vietnam upwelling (SVU) develops off the Vietnamese coast (South China Sea, SCS) during the southwest summer monsoon over four main areas: the northern coastal upwelling (NCU), the southern coastal upwelling (SCU), the offshore upwelling (OFU) and the shelf off the Mekong River mouth (MKU). An ensemble of 10 simulations with perturbed initial conditions were run with the fine-resolution SYMPHONIE model (1 km inshore) to investigate the daily to intraseasonal variability of the SVU and the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The model employed in this study is the Symphonie ocean model (Damien et al, 2017), a three dimensional ocean circulation model solving the primitive equations under Boussinesq and hydrostatic equation. Symphonie has been used in the past over Southeast Asia at several spatial scales, from the Gulf of Tonkin shelf scale (Piton et al, 2021;Nguyen-Duy et al, 2021) and South Vietnam upwelling coastal scale (To Duy et al, 2022;Herrmann et al, 2023) to the South China Sea regional scale (Trinh et al, 2024). Turbulent closure is achieved through the k − ϵ scheme (Burchard and Bolding, 2001).…”
Section: Model Configuration and Overviewmentioning
confidence: 99%
“…The model employed in this study is the Symphonie ocean model (Damien et al, 2017), a three dimensional ocean circulation model solving the primitive equations under Boussinesq and hydrostatic equation. Symphonie has been used in the past over Southeast Asia at several spatial scales, from the Gulf of Tonkin shelf scale (Piton et al, 2021;Nguyen-Duy et al, 2021) and South Vietnam upwelling coastal scale (To Duy et al, 2022;Herrmann et al, 2023) to the South China Sea regional scale (Trinh et al, 2024). Turbulent closure is achieved through the k − ϵ scheme (Burchard and Bolding, 2001).…”
Section: Model Configuration and Overviewmentioning
confidence: 99%
“…Intraseasonal signals of the sea surface temperature (SST) [15], the mixed-layer and upper-ocean temperatures [16], the latent heat flux [17], the sea surface height (SSH) [18], the western boundary current [19], the crossslope flow [20], the subsurface thermocline [21,22], the deep ocean temperature [23], the energy budget [24], and the deep current [25] in the SCS have been widely reported on. As for the summer upwelling area in the western SCS (Figure 1a), the related SST cooling and phytoplankton bloom often experience several intraseasonal events each summer [26][27][28][29][30]. It should be noted that the oceanic intraseasonal signals are not just passive responses to the atmospheric forcing.…”
Section: Introductionmentioning
confidence: 95%
“…Isoguchi and Kawamura (2006) and Xie et al (2007) showed that wind, itself strongly driven by Madden Jullian Oscillation at the intraseasonal summer scale, but also by tropical storms, is a major driver of SVU daily variability. Herrmann et al (2023) more specifically showed that wind is the main driver of daily variability of SEJ and of SCU, OFU and MKU. They showed that NCU variability was rather driven by the strength of the large scale circulation at the intraseasonal scale: the well established circulation and southward boundary current during the core of summer prevent the development along the northern coast of seaward currents, hence of NCU.…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies showed that SVU develops over four main areas (highlighted in Fig. 1), driven by different mechanisms (Da et al, 2019;Ngo and Hsin, 2021;To Duy et al, 2022;Herrmann et al, 2023). The northeastward and southward boundary currents converge near ∼ 14°E, forming the summertime eastward jet (SEJ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation